A Novel Valvuloplasty Scoring Balloon Catheter for Aortic Stenosis. Issue 5 (2nd November 2017) - Htun, Nay M.; Perlman, Gidon Y.; Dvir, Danny; Attinger-Toller, Adrian; Martucci, Giuseppe; Wood, David; Piazza, Nicolo; Webb, John G.
ABSTRACT: Background: There has been a renewed interest in balloon aortic valvuloplasty (BAV) since the inception of transcatheter aortic valve replacement (TAVR) in treating aortic stenosis (AS). This study aimed to demonstrate the safety and feasibility of a novel aortic valvuloplasty balloon catheter for the treatment of symptomatic severe aortic valve stenosis. Methods: Data from 25 patients who underwent BAV with the AngioSculpt Valvuloplasty Scoring Balloon Catheter at two Canadian centers with clinical follow-up and echocardiographic assessment at 30 days, 6 months, and 12 months were analyzed. Results: Mean age of the patients was 83.6 ± 5.8 years with 68% females. Mean gradient across the aortic valve was 44.0 ± 15.1 mmHg pre- and 33.6 ± 13.8 mmHg post-valvuloplasty (average reduction of 24% post-BAV, p  < 0.05). 38% of patients showed ≥ 30% aortic gradient reduction. There were no major adverse cardiovascular events. Stroke and major vascular complication rates were zero. Two patients had moderate aortic regurgitation post-valvuloplasty. Conclusion: Preliminary results with a novel valvuloplasty scoring balloon for aortic stenosis demonstrate no safety concerns with a favorable gradient reduction. Additional studies will be required to demonstrate clinical utility in selected patients.